COVID-19 Cardiac Manifestations and Scent Perception Genes in Hearts of SARS-Cov-2 Infected Patients: A Meta-Analysis of Gene Expression Data: - Roostaei, Davoud; Sohrabpour, Mojtaba; Sanie Jahromi, Mohammad Sadegh; Vatankhah, Majid; Shadmehr, Aghdas; Ebrahimi, Mohsen; Mogharab, Vahid; John Mehramiz, Neema; Foroughian, Mahdi; Hakemi, Arman; Kalani, Navid; Hatami, Naser (Galen Medical Journal, 2021)
Background: COVID-19 induced cardiac events are reported by many papers, while psychophysiology of association of the COVID-19 and cardiac attacks are not fully understood yet. Materials and Methods: Here, we compared gene expression levels of heart autopsies of SARS-Cov-2 infected patients with the cardiac organoid model of human myocardial infarction and controlled healthy cardiac organoids to identify differentially expressed genes (DEGs). Gene Ontology (GO) biological processes were enriched in DEGs. Results: Results showed that smell perception genes were down-regulated in SARS-COV2 compared to myocardial infarction samples; while showing upregulated genes related to the immune system process in contrast to control healthy heart organoids. Our results agree with theories of immune system reactions in COVID-19 infected patients’ hearts, while our analysis indicates different patterns of heart gene expression from myocardial infarction models. Conclusion: our study suggests that there may be other pathways involved in MI appearance in COVID-19 patients rather than classic is known atherosclerotic and inflammatory pathways. [GMJ.2021;10:e2250]